2011
DOI: 10.1136/gutjnl-2011-301501
|View full text |Cite
|
Sign up to set email alerts
|

An irritable bowel syndrome subtype defined by species-specific alterations in faecal microbiota

Abstract: Detailed microbiota analysis of a well-characterised cohort of IBS patients identified several clear associations with clinical data and a distinct subset of IBS patients with alterations in their microbiota that did not correspond to IBS subtypes, as defined by the Rome II criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
571
5
24

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 731 publications
(642 citation statements)
references
References 51 publications
42
571
5
24
Order By: Relevance
“…Another study identified microbiota associated with a distinct subset of IBS patients that did not correspond to IBS subtypes defined by the Rome II criteria (Jeffery et al. 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Another study identified microbiota associated with a distinct subset of IBS patients that did not correspond to IBS subtypes defined by the Rome II criteria (Jeffery et al. 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the quantity of aerobic bacteria and Lactobacillus was noted in IBS-D fecal samples but not in mucosal ones [82]. Elevation in the level of Ruminococcus, Clostridium, Dorea species and a decrease in the quantity of Bifidobacterium and Faecalibacterium species have been demonstrated in IBS [80,[83][84][85][86][87][88][89]. In children, a fecal microbiome characterized by a significantly high percentage of Gamma Proteobacteria and an increased number of several bacterial taxa from the genus Alistipes has been reported in the IBS setting [90].…”
Section: Gastrointestinal Illnesses A) Clostridium Difficile Infectionmentioning
confidence: 80%
“…As well as alterations in specific microbial taxa, reduced diversity, richness and temporal instability are reported in IBS patients v. controls (57)(58)(59)(60) , as well as a greater instability in response to dietary change (61) .…”
Section: Irritable Bowel Syndrome and The Gastrointestinal Microbiotamentioning
confidence: 99%